A Multicentre Based Observation of a Screening tool to Differentiate Microcytosis and Hypochromia - Dipta, Tashmim Farhana; Kabir, Amin Lutful; Rahman, Md Hafizur; Sultana, Gazi Sharmin; Hossain, Ahmed Zahid; Fatema, Nafisa; Ferdousi, Shamima (Anwer Khan Modern Medical College Journal, 2017)
Back ground: Iron deficiency anemia (IDA) and beta-thalassaemia trait (B-TT) are the most common causes of hypochromic microcytic anemia. Many indices have been defined to quickly discriminate these similar entities via parameters obtained from automated blood count analyzers. Methodology: The purpose of the study was to evaluate the predictive value of these indices in differential diagnosis of IDA and B-TT in adult cases. In this study we use auto-analyzer based formula of percentages of microcytic and hypochromic red cells (M/H ratio=% of Microcytosis/% of Hypochromia) as a screening tool for thalassaemia trait in Bangladeshi population. Results: A total of 150 subjects w ere included in this study with 50 known obligate carrier of beta-thalassaemia trait and 100 patients with hypochromia and microcytosis. Confirmatory tests for IDA were performed if serum ferritin level was <12 ng/ml and confirmatory test for Beta-thalassaemia trait (BTT) and Haemoglobin E trait can be considered when HbA2 > 3.5% , on agarose gel Haemoglobin electrophoresis at an alkaline pH (8.6) where, in addition, MCV <76 fl and/or MCH <27 pg. BTT was selected with HbA2 >3.5%, while the non- BTT group were those with HbA2 <3.5%.The final analysis of the result revealed that M/H ratio is a very sensitive index for betathalassaemia trait. In our study, the sensitivity, predictive value and diagnostic accuracy of the M/H ratio for the beta thalassaemia trait were 96%, 90.4% and 90.4% respectively and also identify all cases of coexistent iron deficiency. Conclusion: Thus M/H ratio is an easy, reliable and sensitive index which can be used for mass screening of betathalassaemia trait, particularly in a population where iron deficiency anemia is also prevalent. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 5-10